2016
DOI: 10.1097/rlu.0000000000001284
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG Uptake in Neurosarcoid Dural Plaque on PET/CT

Abstract: While the imaging modality of choice to diagnose neurosarcoidosis is gadolinium-enhanced MRI, F-FDG PET/CT maybe used to stage the disease or target the optimal biopsy site. Few cases have described intense F-FDG uptake at the sites of active neurosarcoidosis in the midbrain and pituitary gland, cerebellar hemispheres, and temporal lobes. Here, we present a case of neurosarcoidosis whose PET/CT examination demonstrated F-FDG avidity in a dural plaque.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…Elevated ACE in CSF is neither sufficiency sensitive nor specific for NS. 27 Of the radiologic studies, PET/CT has been used for identifying active NS 29 it was found helpful for differentiating spinal NS from spinal malignancies. 30 To our knowledge, this technique has not yet been applied for discriminating NS from other inflammatory diseases of CNS.…”
Section: %mentioning
confidence: 99%
“…Elevated ACE in CSF is neither sufficiency sensitive nor specific for NS. 27 Of the radiologic studies, PET/CT has been used for identifying active NS 29 it was found helpful for differentiating spinal NS from spinal malignancies. 30 To our knowledge, this technique has not yet been applied for discriminating NS from other inflammatory diseases of CNS.…”
Section: %mentioning
confidence: 99%
“…С этой целью используют высокопольные магнитнорезонансные томографы с разными режимами исследования и введением пациенту контрастных препаратов на основе гадолиния. Однако неспецифичность нейровизуализационной картины не позволяет создать четкие радиологи- [23,[41][42][43][44][45].…”
Section: проблемы диагностикиunclassified
“…Hypertrophic pachymeningitis should be included in the differential diagnosis of abnormal dural FDG accumulation along with malignant and nonmalignant conditions. [11][12][13][14][15][16][17][18]…”
mentioning
confidence: 99%
“…These 3 cases indicate FDG PET/CT is helpful in identifying the affected dura and evaluating the extent of the inflammatory process. Hypertrophic pachymeningitis should be included in the differential diagnosis of abnormal dural FDG accumulation along with malignant and nonmalignant conditions 11–18 …”
mentioning
confidence: 99%